Green Shells (Perna Viridis L.) Application as A Partial Substitute for Fine Aggregate on Concrete Experiment - Kurniawan, Reyhan Aliev; Prabowo, Yudi Setio (Fakultas Teknik Universitas Tanjungpura, 2026)
The depletion of natural aggregates and the accumulation of shellfish waste necessitate the development of alternative materials for concrete production. This study evaluates the feasibility of using green mussel shell powder (GMSP) as a partial replacement for fine aggregate in concrete. Unlike earlier studies that primarily focus on limited substitution levels, this research systematically examines a broad range of replacement levels (0–50%) to identify the performance threshold for GMSP incorporation. Concrete mixtures were evaluated for 28-day compressive strength, water absorption, and fresh-state workability. The results indicate a nonlinear relationship between GMSP content and compressive strength, with optimal performance at 10% replacement. At this level, a compressive strength of 28.26 MPa was achieved, exceeding the control mixture by 12.8%, attributed to the high CaCO₃ content (77.5%) and associated matrix densification. Higher substitution levels led to a marked reduction in strength due to increased porosity and deterioration of the interfacial transition zone. Although water absorption increased with GMSP content, all values remained within acceptable durability limits. The findings confirm that GMSP from Margaluyu Village is a viable supplementary material, with 10% replacement recommended for optimal structural and sustainability performance.